The Pattern of Malignancies in Down Syndrome and Its Potential Context With the Immune System - Satgé, Daniel; Seidel, Markus G. (Frontiers in Immunology, 2018)
The immune surveillance theory of cancer posits that the body’s immune system detects and destroys randomly occurring malignant cells. This theory is based on the observation of the increased frequency of malignancies in primary and secondary immunodeficiencies, and is supported by the successful demonstration of its augmentation in current oncological immune therapy approaches. We review this model in the context of Down syndrome (DS), a condition with a unique tumor profile and various immune defects. Children and adults with DS are more prone to infections due to anatomical reasons and a varying degree of T- and B-cell maturation defects, NK cell dysfunction, and chemotactic and phagocytic abnormalities. However, despite an increased incidence of lymphoblastic and myeloblastic leukemia of infants and children with DS as compared to non-DS controls, individuals with DS have a globally decreased incidence of solid tumors as compared to age-adjusted controls. Additionally, cancers that have been considered ‘proof of immune therapy principles’, such as renal carcinoma, small cell lung carcinoma, and malignant melanoma, are less frequent in adults with DS compared to the general population. Thus, despite the combination of an increased risk of leukemia with detectable immune biological abnormalities and a clinical immunodeficiency, people with DS appear to be protected against many cancers. This observation does not support the immune surveillance theory in the context of DS and indicates a potential tumor-suppressive role for trisomy 21 in non-hematological malignancies.